Evaluation of prosocial actions performed by dynamic shapes at 17 months of age. Issue 6 (2nd November 2022) - Geraci, Alessandra; Simion, Francesca
ABSTRACT: This research investigated whether the perception of social-causal relation alone triggers both infants' evaluation processes and expectations about the social preferences of informed third parties. Three experiments were carried out, using the violation of expectation (VoE) paradigm. During the familiarization phase, infants saw events in which negative interactions involving two spheres as third parties were presented, while another shape intervened (intervening event) or not (non-intervening event), and a bystander watched these interactions. In Experiment 1, a sphere moved towards another sphere that started to move before the contact (social causality); in Experiment 2, a sphere moved towards another sphere that started to move after the contact (physical causality); in Experiment 3, a sphere moved towards fixed objects (physical causality). In the two test trials, either the intervening or the non-intervening agent needed help to enter into a box, and the bystander helped either agent. Later, a manual choice task assessed infants' preferences. The results demonstrated that only in the social condition infants expected a bystander to help an intervening agent, and preferred the intervening agent. The findings provided evidence that infants' evaluations are triggered by the perception of social causality.